Immune reconstitution after combined haploidentical and umbilical cord blood transplant. Issue 6 (1st June 2013) - Jain, Nitin; Liu, Hongtao; Artz, Andrew S.; Anastasi, John; Odenike, Olatoyosi; Godley, Lucy A.; Joseph, Loren; Marino, Susana; Kline, Justin; Nguyen, Vu; Schouten, Viviane; Kunnavakkam, Rangesh; et al.
Abstract: Umbilical cord blood (UCB) stem cells are frequently employed for allogeneic stem cell transplant, but delayed myeloid and lymphoid immune reconstitution leads to increased risk of infections. We recently reported the clinical results of 45 patients enrolled on a pilot study combining UCB with a human leukocyte antigen (HLA)-haploidentical donor with reduced-intensity conditioning who showed rapid neutrophil and platelet recovery. We report here preliminary immune reconstitution data of these patients. Patients were assessed for lymphocyte subsets, T-cell diversity, Cylex ImmuKnow assay and serological response to pneumococcal vaccination. Natural killer (NK)-cell and B-cell reconstitution were rapid at 1 month and 3 months, respectively. T-cell recovery was delayed, with a gradual increase in the number of T-cells starting around 6 months post-transplant, and was characterized by a diverse polyclonal T-cell repertoire. Overall, immune reconstitution after haplo-cord transplant is similar to that seen after cord blood transplant, despite infusion of much lower cord blood cell dose.